2016
DOI: 10.1007/978-3-319-41603-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Stem Cells Biology: New Approaches to Understand Depression

Abstract: Depression is a highly prevalent complex neuropsychiatric disorder, which ranks first among all mental and neurological disorders as a contributor to the global burden of disease. However, available treatments are still far from ideal, for their specificity as well as their efficacy. This situation can now be improved by the increasing availability of stem cells, which allows the development of in vitro human neural systems to model the brain. These models complement observations from animal models and patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…LTP of synaptic activity in the hippocampus and adult neurogenesis have been implied to play a key role in memory formation and hippocampal-dependent behaviors (Hawkins et al, 1998;Stuchlik, 2014). Impaired hippocampal functions, especially decreased neural plasticity and LTP, contributes to the development of depression (Borsini and Zunszain, 2016;Dina et al, 2017). In current study, we found that liraglutide treatment normalized LTP in the hippocampus after CORT treatment, and promoted adult neurogenesis in hippocampus that had been impaired by CORT ( Fig 3~4).…”
Section: Discussionmentioning
confidence: 99%
“…LTP of synaptic activity in the hippocampus and adult neurogenesis have been implied to play a key role in memory formation and hippocampal-dependent behaviors (Hawkins et al, 1998;Stuchlik, 2014). Impaired hippocampal functions, especially decreased neural plasticity and LTP, contributes to the development of depression (Borsini and Zunszain, 2016;Dina et al, 2017). In current study, we found that liraglutide treatment normalized LTP in the hippocampus after CORT treatment, and promoted adult neurogenesis in hippocampus that had been impaired by CORT ( Fig 3~4).…”
Section: Discussionmentioning
confidence: 99%
“…The germ layers mature into a specific organ. Tissue stem cells can be present in bone marrow, bone, liver, brain, etc., since certain progenitor cells that contributed to organogenesis do not differentiate terminally [ 61 ]. Since they inevitably lead to differentiated cells and specialized cells of the tissue or organ, tissue stem cells are also known as progenitor cells.…”
Section: Stem Cells: An Insightmentioning
confidence: 99%
“…We established that these 14 genes are represented in 33 molecular pathways [56]. The top 3 pathways are represented in Table 2 and it is revealed that each of these pathways have a role in depression and related ailments [57,58,59,60,61]. To validate that these 14 genes do interact and create a network, the STRING database was used to help provide protein-to-protein interaction [62,63].…”
Section: Genomic Interactions Between the Inhibitor Of Dna Bindingmentioning
confidence: 99%